The Lords of Lambityeco : Political Evolution in the Valley of Oaxaca during the Xoo Phase - Lind, Michael (Book collections on Project MUSE., 2010)
"The definitive volume of this Late Classic site. ... an important contribution to Oaxaca archaeology and to understanding Monte Alb at its peak and during its demise." Veronica Perez Rodriguez, American Anthropologist.